Impact of Psychological Comfort on the Interior Design of Patients’ Rooms in Hospitals The General Hospitals in Sulaimani City as a Case Study - Mahmood, Fouad Jalal; Tayib, Abdullah Y. (Sulaimani Journal for Engineering Sciences, 2019)
The aim of the research is to clarify the effect of internal design indicators on improving the efficiency of patients' rooms, to deploy these indicators to be integrated into the curing contexts in achieving healing in a compatible way with the psychological comfort of patients in five public hospitals in Sulaimani city. The contemporary trends in the interior design of hospitals depend on the strong link between the healing environment, which differs from the curing environment by evolving the psychological dimension in the treatment process (curing), and the efficiency of the indoor environment that directly affects the psychological comfort of the patients. The research has adopted a descriptive analytical approach compatible with the nature of the research, using a quantitative measure of the 43-items questionnaire, encompassing six items of psychological comfort including: (Privacy, Views, Comfort & control, Interior appearance, Family support, and Facilities). A total of 240 questionnaires were distributed on the study samples, and then 198 questionnaire forms were retrieved after being completed by the respondents. The percentage of valid questionnaires was 82.5%. The findings of the study showed a positive correlation between internal design indicators and psychological comfort of patients in the patients’ rooms with the possibility of providing a supportive environment for psychological comfort through these indicators. The findings revealed the patients’ satisfaction with the items that support the psychological comfort in the selected hospitals in general and the newly built especially. Also, the findings showed a negative correlation between some demographic characteristics of the patients (age, educational attainment, and duration of stay) and psychological comfort in the patients’ rooms in public hospitals.
Keywords: Psychological dimension; Psychological comfort; Interior Spaces; Healing environment; Hospital interior design